2001
DOI: 10.1007/s002320010060
|View full text |Cite
|
Sign up to set email alerts
|

Actin Modulates the Gating of Neurospora crassa VDAC

Abstract: VDAC forms the major pathway for metabolites across the mitochondrial outer membrane. The regulation of the gating of VDAC channels is an effective way to control the flow of metabolites into and out of mitochondria. Here we present evidence that actin can modulate the gating process of Neurospora crassa VDAC reconstituted into membranes made with phosphatidylcholine. An actin concentration as low as 50 nM caused the VDAC-mediated membrane conductance to drop by as much as 85% at elevated membrane potentials. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 37 publications
5
66
0
Order By: Relevance
“…This scenario seems to reconcile the defects at the level of cytoskeletal organization (1), mitochondrial network (20) and bioenergetics (20,21,24) described in cells from premutation carriers. Furthermore, considering that FMRP regulates the organization and dynamics of actin filaments (50,51), a key process in the morphogenesis of dendritic spines (50), and that actin seems to be involved in mitochondria function and dynamics (48,(52)(53)(54)(55)(56)(57), it could be hypothesized that altered cytoskeletal organization-as a Novartis, Roche/Genentech and Zynerba regarding treatment for fragile X syndrome. formation, inhibits Kreb's cycle, favors ketogenesis and lipogenesis from excess of acetylCoA that did not enter the Kreb's cycle.…”
Section: Resultsmentioning
confidence: 99%
“…This scenario seems to reconcile the defects at the level of cytoskeletal organization (1), mitochondrial network (20) and bioenergetics (20,21,24) described in cells from premutation carriers. Furthermore, considering that FMRP regulates the organization and dynamics of actin filaments (50,51), a key process in the morphogenesis of dendritic spines (50), and that actin seems to be involved in mitochondria function and dynamics (48,(52)(53)(54)(55)(56)(57), it could be hypothesized that altered cytoskeletal organization-as a Novartis, Roche/Genentech and Zynerba regarding treatment for fragile X syndrome. formation, inhibits Kreb's cycle, favors ketogenesis and lipogenesis from excess of acetylCoA that did not enter the Kreb's cycle.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown that in neuronal cells the antiapoptotic activity of gelsolin is actin dependent (Harms et al, 2004). In vitro studies have also demonstrated that actin can influence VDAC closure in Neurospora crassa (Xu et al, 2001). However, in our studies, the overexpression of the antiapoptotic proteins Bcl-2 or BclxL, which are known to regulate VDAC closure, in ∆end3 cells have no effect on H 2 O 2 sensitivity or culture viability (C.W.G.…”
Section: Discussionmentioning
confidence: 97%
“…Taken together, these results suggest that the contact site may be involved in the import of actin from the cytosol, and actin dynamics at the contact site may affect the opening and closure status of the mPTP. Actin has been shown to be capable of modulating the gating process in Neurospora crassa voltage-dependent anion channel (VDAC) (Xu et al, 2001).…”
Section: Discussionmentioning
confidence: 99%